2007
DOI: 10.1007/s00415-006-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal stenosis: Assessment of cauda equina involvement by electrophysiological recordings

Abstract: Whereas the clinical examination, even in severe LSS, showed no specific sensory-motor deficit, the electrophysiological recordings indicated that the majority of patients had a neurogenic disorder within the lumbar spine. By the pattern of bilateral pathological tibial SSEP and pathological reflexes associated with normal peripheral nerve conduction, LSS can be separated from a demyelinating polyneuropathy and mono-radiculopathy. The applied electrophysiological recordings, especially SSEP, can confirm a neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The VAS was divided into four groups: absent (0-1), moderate (2-4), strong (5-7) and very severe pain or numbness (8)(9)(10). The JOA scores of clinical signs (SLR test, sensory and motor disturbances) and VAS scores for back pain, leg pain and leg numbness are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The VAS was divided into four groups: absent (0-1), moderate (2-4), strong (5-7) and very severe pain or numbness (8)(9)(10). The JOA scores of clinical signs (SLR test, sensory and motor disturbances) and VAS scores for back pain, leg pain and leg numbness are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…24,54 Electromyography may also be helpful in reaching a diagnosis. 17 Ultimately, like several of the conditions described in this review, these conditions may occasionally coexist in the same patient.…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…Katz et al 8) reported that the more than 30,000 surgical procedures were performed in United States in 1994 to treat LSS. The rate of diagnosis is growing rapidly because of improvements in diagnostic imaging tools and surgical techniques, and the aging of the population 4) . The cardinal symptom of LSS is neurogenic claudication, defined as pain in the buttocks and legs, and numbness or cramping of one or both legs induced by walking, which is relieved when sitting and bending forward 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Neurological deficits, such as leg motor weakness and cauda equina syndrome are not common in LSS patients, because neural compression is relieved by positional change 6) . In particular, the LSS symptom of rapidly progressing leg weakness must be distinguished from other causes, such as combined diseases or trauma 4) . In the case presented here, whole spine MRI and EMG/NCV showed LSS at L4-5 and radiculopathy in L4, L5, S1 with mild diabetic neuropathy, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation